2017
DOI: 10.1111/1556-4029.13690
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the Count: Improving Vital Statistics Data Regarding Deaths Related to Obesity

Abstract: Obesity can involve any organ system and compromise the overall health of an individual, including premature death. Despite the increased risk of death associated with being obese, obesity itself is infrequently indicated on the death certificate. We performed an audit of our records to identify how often "obesity" was listed on the death certificate to determine how our practices affected national mortality data collection regarding obesity-related mortality. During the span of nearly 25 years, 0.2% of deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As noted earlier, the only currently-available ICD coding options that specifically implicates obesity as the underlying cause of death are the E66-67 codes, which likely heavily undercount obesity-related deaths -as demonstrated in this analysis and suggested in earlier work (16,(27)(28)(29). Thus, it is inevitable that at least some proportion of the deaths in each scheme are not due to obesity, but instead a function other lifestyle and health factors, such as smoking (17).…”
Section: Limitationsmentioning
confidence: 62%
See 2 more Smart Citations
“…As noted earlier, the only currently-available ICD coding options that specifically implicates obesity as the underlying cause of death are the E66-67 codes, which likely heavily undercount obesity-related deaths -as demonstrated in this analysis and suggested in earlier work (16,(27)(28)(29). Thus, it is inevitable that at least some proportion of the deaths in each scheme are not due to obesity, but instead a function other lifestyle and health factors, such as smoking (17).…”
Section: Limitationsmentioning
confidence: 62%
“…It is an overly narrow definition of obesity-related deaths, which necessitates that obesity is listed as not only a cause of death on the death certificate, but as the underlying cause. Unfortunately, this strict criterion is potentially subject to the biases/assumptions of the person coding the cause of death (27,29), leading to the identification of less than a fifth of all deaths where obesity is implicated (24). For instance, a cross-national comparison of obesity-related mortality suggests that physicians' propensity for reporting obesity as an underlying cause on death certificates might vary due to their "sensitiv[ity] to abnormally high BMIs," in reference to national differences in the prevalence of obesity and thus expectations about the average BMI and body size (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics demonstrated that the consumption of simple carbohydrates, especially fructose and sucrose, is increasing worldwide (22). A diet rich in carbohydrates or fats, inactivity, and genetic background are the most critical factors in obesity and related diseases such as hyperlipidemia and diabetes (23). Obesity directly affects the incidence of cardiovascular disease as the leading cause of death worldwide (24).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the mortality databases of the Pan American Health Organization (PAHO) for the region of the Americas [17] found that the use of the E66 code for certifying obesity as the underlying cause of death increased from 4,050 in 1999 to 12,087 in 2015, with the USA accounting for 64.4% and 61.1% of these deaths, respectively. The underreporting of obesity as a cause or contributing factor to death can lead to underestimations in regard to the effect of obesity on mortality [18][19][20].…”
Section: Introductionmentioning
confidence: 99%